2019
DOI: 10.1111/add.14722
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of cigarette smoking dependence and relapse in former smokers who vape compared with those who do not: findings from the 2016 International Tobacco Control Four Country Smoking and Vaping Survey

Abstract: Background and Aims It has been proposed that many smokers switch to vaping because their nicotine addiction makes this their only viable route out of smoking. We compared indicators of prior and current cigarette smoking dependence and of relapse in former smokers who were daily users of nicotine vaping products ('vapers') or who were not vaping at the time of survey ('non-vapers'). Design Cross-sectional survey-based comparison between vaping and non-vaping former smokers, including a weighted logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Few other studies have examined the role of NVPs in smoking relapse. One study found that vaping may be protective against relapse [ 14 ], but similar to our study, Brose et al [ 36 ] reported that there was no difference in relapse between exclusive daily vapers compared to those who were not vaping. However, they did find that ex-smokers who vaped infrequently had a higher probability of relapse, suggesting that this group of ex-smokers were not vaping enough to satisfy their cravings for nicotine.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Few other studies have examined the role of NVPs in smoking relapse. One study found that vaping may be protective against relapse [ 14 ], but similar to our study, Brose et al [ 36 ] reported that there was no difference in relapse between exclusive daily vapers compared to those who were not vaping. However, they did find that ex-smokers who vaped infrequently had a higher probability of relapse, suggesting that this group of ex-smokers were not vaping enough to satisfy their cravings for nicotine.…”
Section: Discussionsupporting
confidence: 86%
“…However, some caution is required when interpreting population-based studies as NVP use is not randomized and there is reason to believe those vaping differ from those who are not. For example, concurrent users have been shown to be more dependent on nicotine than smokers who do not vape [ 14 , 15 ]. Further, baseline smokers who use NVPs could be viewed as “treatment failures” if they initiated NVP use to help them to stop smoking, but had not quit at the time of the follow-up survey.…”
Section: Introductionmentioning
confidence: 99%
“…Vaping and also use of NRT may be a marker of higher dependence on nicotine which is consistently associated with increased relapse [25]. This is supported by evidence that vapers were more likely than non-vapers to report higher cigarette dependence when they were smoking [26]. Infrequent use and thus nicotine consumption would not sufficiently protect against this increased risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Such socioeconomic patterning in e-cigarette use is important, considering that studies have shown that those who formerly smoked and now vape reported greater confidence in not smoking compared with those who do not vape. 16,24 This is contextualized by the absence of a trend in the use of nicotine replacement therapy, another widely available nicotine product, across the period. However, a 2019 randomized clinical trial that showed e-cigarettes to be almost twice as effective for smoking cessation at 1 year compared with nicotine replacement therapy 3 has indicated that, in the context of the trial, the devices may not confer extra protection against relapse.…”
Section: Jama Network Open | Substance Use and Addictionmentioning
confidence: 99%